2015
DOI: 10.1152/japplphysiol.00403.2015
|View full text |Cite
|
Sign up to set email alerts
|

Doublet potentiation in the triceps surae is limited by series compliance and dynamic fascicle behavior

Abstract: Activation of skeletal muscle twice in quick succession results in nonlinear force summation (i.e., doublet potentiation). The force contributed by a second activation is typically of augmented amplitude, longer in duration, and generated at a greater rate. The purpose of this study was to examine force summation in a muscle attached to a compliant tendon, where considerable internal shortening occurs during a fixed-end contraction. The triceps surae of 21 (Experiment 1) and 9 (Experiment 2) young adults were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…Though shortening velocity was not measured in the present study, a higher velocity of shortening can be inferred from the larger amplitude of shortening permitted in the presence of additional series compliance. High velocities of shortening under constantlength conditions, and in response to high-frequency doublet stimulation, have previously been demonstrated in vivo for a muscle group with a compliant tendon (Mayfield et al, 2015). A significant reduction in the rate of force development under the compliant conditions imposed in the present study suggests that the fibre bundles did in fact operate at velocities at which force production is considerably limited (Hill, 1938).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Though shortening velocity was not measured in the present study, a higher velocity of shortening can be inferred from the larger amplitude of shortening permitted in the presence of additional series compliance. High velocities of shortening under constantlength conditions, and in response to high-frequency doublet stimulation, have previously been demonstrated in vivo for a muscle group with a compliant tendon (Mayfield et al, 2015). A significant reduction in the rate of force development under the compliant conditions imposed in the present study suggests that the fibre bundles did in fact operate at velocities at which force production is considerably limited (Hill, 1938).…”
Section: Discussionsupporting
confidence: 64%
“…When a second pulse is delivered during the early rise in twitch force, before or immediately after the peak in fibre shortening velocity, a higher peak velocity of shortening is achieved. For instance, individual muscles of the human triceps surae achieve peak velocities during a highfrequency doublet that are 50% higher than during a twitch (Mayfield et al, 2015). We argue that the higher velocity of active shortening afforded by the compliant tendon was sufficient to cause a considerable reduction in the force-generating capacity of the contractile apparatus during force development, such that the relative force contribution of a second stimulating pulse was reduced with respect to stiffer conditions.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The lack of change in 20:VFT suggests that a decreased Ca 2+ sensitivity was not an overriding factor affecting force production following the fatiguing exercise. It is important to note, however, that because of the large compliance in the plantar flexor muscle–tendon unit (due particularly to the long Achilles tendon) the effect of the doublet stimulation on force production may be minimized when compared to other muscle groups such as the knee extensors (Binder-Macleod and Kesar, 2005; Mayfield et al, 2015) and this may have reduced our ability to detect small changes in the 20:VFT ratio. On the contrary, it might be the case that the doublet has a minimal effect in the plantar flexors and therefore a loss of the ability to use it, i.e., changes in Ca 2+ sensitivity may not be important.…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted work in a muscle group that does not demonstrate greater than linear force summation under constantlength conditions and suggested that muscle-tendon interaction may have additional implications for force summation (Mayfield et al, 2015). Force summation in response to doublet stimulation was shown to be to be comparatively low for the human triceps surae, a group of muscles arranged in-series with a long, elastic tendinous element (i.e.…”
Section: Introductionmentioning
confidence: 99%